SPIRITUAL ENTREPRENEURSHIP BERBASIS AL-QUR’AN - Sodiman Sodiman (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
Abstract Ian Marshall and Danah Zohar predicted theoretically that in the context of modern business will appear spirituality without religion as the moral basis of the business which he described as spiritual capital. But look at the phenomenon in Indonesia, sharia economic development is rapidly increasing which in fact appears based on religious values, then the theory Marshal and the Zohar indisputable. Spiritual entrepreneurship based on the Koran in Indonesia is growing; the ideas, thoughts, willingness (iradah), passion (ghirah) and determination ('azm) owned by an individual or group (community) Muslims to strive in commerce (material or services) that are based on the values of faith in God who taught the Koran. Spirituality entrepreneurship models based al-Qur'an that life (living values) is very varied, among the models discussed in this paper are (1) spirituality entrepreneurship kaafah models, (2) spirituality entrepreneurship ukhuwah models, (3) spirituality entrepreneurship tareqat models, (4) spirituality entrepreneurship models keep ablution, (5) spirituality entrepreneurship models do not sell cigarettes, (6) the spirituality of entrepreneurship model- publication that profit to charity. Key Words : Spiritual, entrepreneurship, and models of bussines.